Developing Science-Based Modules with MIKiR and Literacy Learning in the Grade V - Asmaryadi, Ahmad Ilham (PPSDP International Journal of Education, 2023)
The background problem in this research is the inactivity of students during learning activities, especially in science lessons, which is caused by the lack of learning resources used by educators. This is because the teacher does not have teaching materials such as modules so that the learning process only takes place using teacher books and student books. The efforts made by the author to provide solutions to the problems that occur at Elementary School by producing a companion module for science based on MIKiR learning and literacy. The importance of developing teaching materials for companion modules in learning activities experienced by educators and students. This research is a development research using the ADDIE form. This research was carried out in several stages, namely the Analysis, Design, Development, Implementation, and Evaluation stages. The results of the validation research by three validators have a score of 86% which can be categorized as very valid. The results of the practicality assessment of the companion module conducted by the teacher and fifth grade Elementary School students got a score of 90.39% which was categorized as very practical. The results of the effectiveness carried out by fifth grade Elementary School students obtained a percentage of completeness 80% with a very effective category. It was concluded that the development of a science companion module based on experience, interaction, communication, reflection (MIKiR) and literacy learning had valid, practical, and effective criteria.